Sypané vulkanické kužele na Měsíci: jejich morfologie, rozmístění a mechanismus jejich vzniku - Novotný, Radek (Univerzita Karlova, Přírodovědecká fakulta, 2019)
The recent observations of the Moon show, that there was long-lasting volcanic activity on the lunar surface, that left many volcanic features behind. These features are in the form of lunar seas, which are covering thousands of kilometers wide impact basins, or small volcanic bodies of various shapes. Some of these bodies are relatively small, up to 170 meters high conical bodies occurring on the near side and far side of the Moon. Based on research about the Marius Hills and South Pole-Aitken locations, it was suggested, that these bodies could be a lunar equivalent of terrestrial cinder cones. Cinder cones are created by degassing and fragmentation of magma with subsequent deposition of pyroclastic material into the surroundings. This shape similarity of the lunar cones to the terrestrial cones is surprising, as there is less gravitational acceleration on the Moon's surface and the atmosphere is missing. This means, that particles are able to flow further, and this should also affect the appearance of the volcanic bodies. The aim of this work is to review available literature mentioning lunar cones, to map their frequencies on the surface of the Moon, to determine their basic shapes and explain possible differences or concordances in their shapes with terrestrial cinder cones. On the basis of the. Pozorování Měsíce moderními přístroji dokládají, že na povrchu dříve probíhala dlouhodobá sopečná činnost zanechávající za sebou řadu povrchových útvarů, ať už v podobě měsíčních moří pokrývající tisíce kilometrů široké impaktní pánve či v podobě malých sopečných těles různých tvarů. Jedním z nich jsou i relativně malá, až 170 metrů vysoká kuželovitá tělesa vyskytující se na přivrácené i odvrácené straně Měsíce. Na základě výzkumu lokalit Marius Hills a South Pole-Aitken bylo navrženo, že by se mohlo jednat o měsíční obdobu pozemských sypaných kuželů. Tedy těles vznikající odplyněním a fragmentací magmatu s následným ukládáním pyroklastického materiálu do okolí. Tato tvarová podobnost měsíčních kuželů s pozemskými ...